2008
DOI: 10.1111/j.1365-2036.2008.03694.x
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review: gastro‐oesophageal reflux disease and dental lesions

Abstract: SUMMARY BackgroundDental erosion (DE), which is the irreversible loss of tooth substance that does not involve bacteria ranging from a minimal loss of surface enamel to the partial or complete exposure of dentine by a chemical process, is acknowledged as an established extra-oesophageal manifestation of gastro-oesophageal reflux disease (GERD). However, the real impact of GERD in the genesis of this lesion remains unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
98
2
18

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(122 citation statements)
references
References 29 publications
4
98
2
18
Order By: Relevance
“…On the other hand, despite a wide range of the rate of dental erosions in patients with GERD in different populations (3,4), the prevalence of DE is higher more than 3 times in comparison to our findings in a study in one of our referral university clinics (5). It may arise from social and cultural differences affecting extrinsic factors like food and beverage consumption or oral hygiene.…”
Section: Dear Editorcontrasting
confidence: 54%
“…On the other hand, despite a wide range of the rate of dental erosions in patients with GERD in different populations (3,4), the prevalence of DE is higher more than 3 times in comparison to our findings in a study in one of our referral university clinics (5). It may arise from social and cultural differences affecting extrinsic factors like food and beverage consumption or oral hygiene.…”
Section: Dear Editorcontrasting
confidence: 54%
“…Few studies have linked dental caries to GER, and there is no consensus on whether patients with this condition have a greater or lesser caries experience when compared to healthy individuals. 25,27 Some studies demonstrate that GER is associated with the development of dental caries, 28 whereas other studies report that this disorder plays a protective role against dental caries.…”
mentioning
confidence: 99%
“…24 Gastroesophageal reflux (GER) is another common characteristic in this group of patients, and this condition has been investigated as a potential causal agent of dental caries. Tooth erosion is an oral condition that has been associated 25 with or has indicated 26 GER disease. Few studies have linked dental caries to GER, and there is no consensus on whether patients with this condition have a greater or lesser caries experience when compared to healthy individuals.…”
mentioning
confidence: 99%
“…Jarvinen et al [20] examined 109 patients with upper gastrointestinal symptoms and found only 6.4% to have erosion, while Meurman et al [21] found 26.2% out of 107 patients diagnosed with gastro-esophageal reflux to have dental erosion. For Pace F et al [22], the median prevalence of dental erosion in GERD patients was 24%, with a large range (5-48%), and the median prevalence of GERD in adult patients with dental erosion was 32.5% (range 21-83%), while in pediatric patients it was 17% (range 14-87%).…”
Section: Resultsmentioning
confidence: 99%